Reconsidering Burke’s and Arendt’s Theories on “The Rights of Man”: A Surprising Plot Twist? - Chountis, Ioannes (Conatus - Journal of Philosophy, 2021)
Edmund Burke can perhaps be considered as the father of modern conservatism. Hannah Arendt was a very eclectic thinker who embraced ideas from the traditions of liberalism and republicanism. They both commented on the issue of the “Rights of Man” and rejected their abstract and metaphysical nature. And, it was Arendt who saw a ‘certain pragmatism’ in Burke’s ideas. Is this coincidence of opinion a surprising plot twist? An unintentional ‘alliance’ against the naturalness of the “Rights of Man?” This paper first discusses the real relationship between Burke’s and Arendt’s theories on human rights. In the first part, the ideas of the two thinkers are presented and examined. In the second part, the main convergences and divergences are identified. Through a careful reading of the Burkean and Arendtian corpus, it is shown that Arendt agreed with Burke that human rights cannot be abstract or metaphysical. On the other hand, Arendt, being autonomous in her critique, argued for one universal and inalienable right, that is ‘the right to have rights,’ i.e. the right to belong to political community. In overall, the analysis endeavors to provide an answer to the question as to what degree did Arendt endorse Burke’s theories on the “Rights of Man.”